Implementation of an outline of transformer induced voltage tests - Orestes Hernández Areu; Gualfrido Hernández Puentes; Miguel A. Ramírez Moreno; Alberto C. Ayala Anaya (Revista Cubana de Ingeniería, 2010)
The results of the developed work for the implementation of the induced voltage test to be applied to single phase distribution transformers in the Researches and Electroenergetic Tests Center (CIPEL) of Cuba, are presented, The test outline was obtained starting from the employment of a motor - generator group, with an external voltage regulator and using a frequency converter to obtain the necessary frequency for this type of test.